Menumbuhkan Semangat Fastabiqul Khairat Melalui Bilangan Riil - Lusi Englita; Ferry Fernando (Journal on Education, 2025)
The sentence fastabiqul khairat which is translated as "competing in goodness" is the invitation of Allah subhanahu wata’ala so that people are enthusiastic in charity. To increase the spirit of fastabiqul khairat among mathematics students, it can be given through lectures on real number material. Real numbers are represented as directed lines (real lines), where there is a fixed point 0, to the right is positive and to the left is negative. This real line is metaphorically like human charity, the origin 0 represents the situation when a person has neither reward nor sin (like a newborn baby) or when they have the same proportion of good and bad charity. When people do a good charity , they will get the reward and the position moves to the right (positive direction), but if they do something bad, the charity points move to the left (negative direction). Keywords: fastabiqul khairat, real number, reward, sin